Sur Les Rapprochements Par Conjugaison en Dimension 1 Et Classe c1 - Navas-Flores, A (Cambridge University Press, 2014)
We show that the space of actions of every finitely generated, nilpotent group by C1 orientation-preserving diffeomorphisms of the circle is path-connected. This is done via a general result that allows any given action on the interval to be connected to the trivial one by a continuous path of topological conjugates. © 2014 The Author.